Multi-planar instability, laxity and reduced knee flexion during the support phase of walking are determinants of return to sports - Zhou, Tianping; Xu, Yihong; Zhou, Lan; Wang, Siya; Wang, Shaobai; Xu, Weidong (Frontiers in Bioengineering and Biotechnology, 2022)
Background: After anterior cruciate ligament reconstruction, some patients are not recommended to return to high-level physical activity because they fail to pass return-to-sports tests. The kinematic difference between these patients and those who pass the return-to-sports tests is unclear. Methods: Eighty-two patients who received anatomic single-bundle anterior cruciate ligament (ACL) reconstruction for unilateral ACL injury underwent return-to-sport tests during a hospital visit at a minimum of 9 months (9-11 months) of follow-up. Fifteen patients who passed the return-to-sports tests (RTS group) and fifteen patients who did not (NRTS group) were randomly selected to perform a treadmill walk under dual-fluoroscopic imaging system surveillance for a 6 degrees of freedom kinematic evaluation. Results: Of the 82 patients, 53 passed the return-to-sports tests 9 months after surgery, with a return-to-sports rate of 64.6%. In the stance phase, the NRTS group had a larger anterior tibial translation (1.00±0.03mm vs. 0.76±0.03mm， P＝0.001), a larger lateral tibial movement (1.61±0.05mm vs. 0.77±0.05mm， P<0.001), a larger distal tibial displacement (-3.09±0.05mm vs. -2.69±0.05mm， P<0.001), a smaller knee flexion angle (6.72±0.07° vs. 8.34±0.07°， P<0.001), a larger varus angle (-0.40±0.03 °VS -0.01±0.03°， P<0.001) and a larger external rotation angle (1.80±0.05° vs. 1.77±0.05°， P<0.001) than the RTS group. The maximum anterior tibial translation of the NRTS group is also larger than that of the RTS group (3.64±0.42mm vs. 3.03±0.59mm， P＝0.003). Conclusion: Compared with patients passing RTS tests, those who fail to pass show significant anterior, lateral, and rotational instability; knee laxity; and reduced flexion angle of the knee in the support phase during walking, which may be the possible factors hindering a return to sports.